The Emergence of Shell Valuable Exchange in the New Guinea Highlands. Issue 1 (18th December 2018) - Gaffney, Dylan; Summerhayes, Glenn R.; Szabo, Katherine; Koppel, Brent
ABSTRACT: Shell valuable exchange in the New Guinea Highlands has been a key interest in anthropology, providing insight into economics, aesthetics, and social stratification among banded communities. This article describes how shell exchange at ethnographic present reflects deeper historical processes. We trace the origins and subsequent changes in shell use from the terminal Pleistocene to the Late Holocene at the site of Kiowa in Chimbu Province, Papua New Guinea. Zooarchaeological and technological analyses of Kiowa's shell artifacts indicates riverine mussel was procured locally from the terminal Pleistocene (9, 500–10, 000 years ago) and featured as a minor component in the diet into the recent precolonial period. In contrast, evidence for marine shell valuables only appears in the Late Holocene in the form of Trochus armbands and Tegillarca granosa and Polymesoda cf. erosa multifunctional tools. This challenges ideas that associate the gradual dispersal of marine shell into the highlands with the spread of agriculture around the Wahgi Valley at the start of the Holocene and supports punctuated pulses of coastal contact. In doing so, we formulate a testable model for the development of shell exchange into the highlands, with implications for the emergence of stratification and the conduits between the interior and coast. [ shell valuables, trade and exchange, coastal contact, stratification, New Guinea Highlands ] RESUMEN: El intercambio valioso de conchas en la zona montañosa de la Nueva Guinea ha sido un interés clave en antropología, proveyendo conocimiento en la economía, la estética y la estratificación económica entre las comunidades congregadas. Este artículo describe cómo el intercambio de conchas en el presente etnográfico refleja procesos históricos más profundos. Trazamos los orígenes y los cambios subsecuentes en el uso de conchas desde el Pleistoceno terminal al Holoceno tardío en el sitio de Kiowa en la provincia de Chimbu, Papúa Nueva Guinea. Los análisis zooarquelógicos y tecnológicos de artefactos de conchas en Kiowa indican que el mejillón fluvial se obtuvo localmente desde el Pleistoceno terminal (9.500–10.000 años atrás) y se incluyó como un componente menor en la dieta en el período precolonial reciente. En contraste, la evidencia de objetos de valor de las conchas marinas sólo aparece en el Holoceno tardío en la forma de brazaletes de Trochus y herramientas multifuncionales de Tegillarca granosa y Polymesoda cf. erosa. Esto reta ideas que asocian la dispersión gradual de las conchas marinas en la zona montañosa con la expansión de la agricultura alrededor del Wahgi Valley al principio del Holoceno, y apoya pulsos intermitentes de contacto costero. De este modo, formulamos un modelo comprobable para el desarrollo del intercambio de conchas en la zona montañosa, con implicaciones para la emergencia de estratificación y los conductos entre el interior y la costa. [ objetos de valor de conchas, comercio e intercambio, contacto costero, estratificación, Zona montañosa de Nueva Guinea ]